The mutiny of the elsinore, with ebook eaudiobook - London, Jack (Tantor Media, 2009)
Life has lost its savor for Mr. Pathurst. New York, fame, women, and the arts have all become tedious. Searching for excitement, he books passage on a cargo vessel sailing from Baltimore to Seattle on a route that travels around the treacherous Cape Horn. Pathurst encounters more than he ever expected in rough seas, turbulent storms, and a mutinous crew. His epic struggles aboard the sailing ship Elsinore have given him a new love for life, but will he survive to profit from it? Everyone who remembers The Sea Wolf with pleasure will enjoy this vigorous narrative. The Mutiny of the Elsinore is the same kind of tale as its famous predecessor, and it has been pronounced even more stirring by those who have read it. Jack London writes of scenes and types of people with which he is very familiar: the sea and ships and those who live in ships. In addition to the adventure element, of which there is an abundance of the usual London kind, there is a thread of romance. The play of incident—on the one hand the ship's amazing crew and on the other the lovers—results in a story that demonstrates anew what a master of his art the author is.